University extension and its relationship with the quality of life of vulnerable elderly amazonians (Research, Society and Development, 2021)
Objective: to report the experience of activities carried out in a university extension project with the elderly, where participatory methodologies were used to value the social and cultural issues of those involved. Methodology: This is a qualitative, descriptive study, an experience report type. This experience report was elaborated from the experiences of the university extension project “Healthy Elderly”, linked to the curricular activity Integral Attention to Adult and Elderly Health of the third period of the Nursing course at the Federal University of Pará (UFPA) Result: The the development of activities with the elderly is essential to stimulate active aging and with quality of life, such that the process of professional training in gerontogeriatrics is increased, since nursing students participate in the project. Final considerations: Extension activities are an important link between the university and communities. The impact on the quality of life of the elderly participants was observed, as well as on the broader and more specialized view of the aging process, in addition to the importance of strengthening studies in the area to effect the protagonism and impact on the elderly population.